Assessment of cognitive profile as a prodromal marker of the evolution of rapid eye movement sleep behavior disorder. Issue 8 (23rd April 2019) - Terzaghi, Michele; Toscano, Gianpaolo; Casoni, Francesca; Picascia, Marta; Arnaldi, Dario; Rustioni, Valter; Versino, Maurizio; Sinforiani, Elena; Manni, Raffaele
Abstract: Study Objectives: To search for a specific neuropsychological profile in idiopathic REM sleep behavior disorder (iRBD), able to predict the onset of neurodegenerative disorders. Methods: In a longitudinal follow-up study of 63 consecutive iRBD patients (follow-up duration 6.7 ± 3.8 years), the baseline cognitive profile of converters to neurodegenerative disease was compared with that of the nonconverters. Five cognitive domains were assessed: memory, attention-working memory, executive functions, visuospatial abilities, language. Mild cognitive impairment (MCI) was diagnosed according to the Movement Disorder Society's diagnostic criteria for Parkinson's disease. Results: 30 subjects (47.6%) developed a neurodegenerative disease (latency to conversion 60.33 ± 44.81 months). MCI was found in 50% of the converters and 12% of the nonconverters (p = .001), and its presence conferred a neurodegenerative disease risk of 10% at 3 years, 36% at 5 years, and 73% at 10 years (p = .002). Pathological equivalent scores on at least one neuropsychological test were detected in 46.7% of the converters versus 21.2% of the nonconverters in the memory domain (p = .032), in 40.0% versus 6.1% in that of executive functions (p = .002), and in 20.0% versus 3% in the visuospatial abilities domain (p = .047). On multivariate analysis, impaired executive functions significantly correlated with phenoconversion (p = .018). Lower Mini Mental State Examination (MMSE) scores (p = .004) and memory deficits (p = .031) were found in patients who developed dementia first. Conclusions: Cognitive profile is useful for stratifying risk of phenoconversion in patients with iRBD. The presence of MCI and impaired executive functions, memory, and visuospatial abilities discriminated the converters. Lower MMSE scores and memory deficits may characterize those subjects who first develop dementia.